CRITICAL ANALYSIS OF NURSING TECHNICIAN ROLES IN PERIOPERATIVE CARE. - Saeed Mahmoud Al Juhayf, Hassan Mohammed Salem Alrabie, Mohammed Mahdi Maree Al Abbas, Hamad Suliman Nasser Alkurbi, Nouf Ali Marzooq Alyami, Saleh Mana Mohammad Almasad, Mohammed Ali Mutlaq Al Jumhur, ‎Nasser Muhammad Hamad Bani Hamim (Chelonian Research Foundation, 2023)
This article aims to critically examine the important role of nursing technicians in the perioperative care process. While familiarizing ourselves with routine and arduous tasks, it also aims to teach everyone the role of nurses in the perioperative team. This analysis will focus on nursing technicians by privileging a blend of literature and evidence-based information to reveal how they aid in improving patient outcomes and making operative procedures more efficient. A nursing technician performs perioperative activities before, during, and after an operation, which is crucial in facilitating the smooth running of surgical procedures and ensuring patients' well-being. This presentation will, therefore, focus on the indispensable role of nursing technicians in the perioperative care continuum and the call for the recognition and support needed to continue to flourish the nurses as they advance and excel in this field of medicine. Keywords: Nursing technicians, perioperative care, surgical assistance, patient outcomes, healthcare optimization